Small cross mapping of flowering time determinants - Cuesta-Marcos A.; Casas A.M.; van Eeuwijk F.; Lasa J.M.; Gracia M.P.; Igartua E. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Seventeen small populations of doubled haploid lines, from representative crosses of the Spanish public barley breeding program were used. The field trials consisted of three replications of two-row plots, 1m long, following a randomized complete block design. Heading date was recorded as the moment when 50 percent of the tillers exhibited 2 cm of protruding awns. We used 72 markers covering all the genome, specially the areas involved in flowering time, according to previous studies. Linked markers were used for the photoperiod gene Ppd-H2 and some earliness per se genes. Some spring x spring and winter x winter populations, for which no polymorphic markers were found in these regions, were genotyped with 8 more markers in chromosome 6H. A consensus map of the 17 populations was constructed using Joinmap 3.0. In a first step, individual markers were analyzed, with the marker main effect as a fixed term and the marker by population interaction as a random term. In the next step, multiple marker models were used, where all significant markers, but the marker that is being specifically analyzed, were included as co-factors. Rare alleles were not included in the analyses.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)